Bimetallenes for selective electrocatalytic conversion of CO2: a first-principles study. Issue 25 (16th June 2020) - Zhao, Zhonglong; Lu, Gang
Abstract : Two-dimensional bimetallenes are explored for the first time as promising electrocatalysts for CO2 conversion by extensive first-principles calculations. Abstract : Two-dimensional (2D) materials are full of surprises and fascinating potential. Motivated by a recent discovery that sub-nanometer PdMo bimetallenes can realize exceptional performance in the oxygen reduction reaction [ Nature 2019, 574, 81–85], we explore the potential of 2D bimetallenes for catalyzing the CO2 electroreduction reaction (CO2 RR). Following extensive first-principles calculations on more than a hundred bimetallenes, we identify 17 Cu- and Ag-based bimetallenes, which are highly active and selective toward the formation of formic acid and simultaneously suppress the competing hydrogen evolution reaction. Equally important, we find that CO2 RR products via intermediates of COOH and CO are disfavored on these bimetallenes. Although surface strains are developed on the bimetallenes, their contribution to the catalytic activities is moderate as compared to that of the alloying effect. This work opens the door to future applications of bimetallenes as active and selective catalysts for the CO2 RR.